2021
DOI: 10.1002/jid.3574
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of the effect of tobacco taxation on economic growth in 38 African countries

Abstract: Globally, tobacco use claims millions of lives every year. This has necessitated policy responses including tax measures aimed at reducing the consumption of tobacco. Nonetheless, opponents of tobacco taxation posit that, it may hurt economic growth. This study, therefore, examines the effect of tobacco taxation on economic growth in 38 African countries from 2008 to 2018. The system generalised method of moments (GMM) regression is used as the estimation technique. The findings show that, tobacco taxation enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The negative and positive effects of consumption expenditure and domestic investment, respectively, on economic performance are not farfetched because, while consumption serves as a leakage and hence reduces productive capacity, investment serves as an injection, which increases productive capacity, hence, economic performance [ 22 ]. Our finding on domestic investment is in tandem with Ibrahim and Alagidede [ 42 ], Egyir et al [ 25 ], and Oyebowale and Algarhi [ 43 ] who found investment to enhance economic growth in Africa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The negative and positive effects of consumption expenditure and domestic investment, respectively, on economic performance are not farfetched because, while consumption serves as a leakage and hence reduces productive capacity, investment serves as an injection, which increases productive capacity, hence, economic performance [ 22 ]. Our finding on domestic investment is in tandem with Ibrahim and Alagidede [ 42 ], Egyir et al [ 25 ], and Oyebowale and Algarhi [ 43 ] who found investment to enhance economic growth in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Turning to the control variables, the effect of FDI on economic performance is uncertain. This is because, FDI can be detrimental to economic performance by crowding out domestic investment [ 22 , 29 ], while on the other hand, FDI can be associated with higher factor productivity in the recipient country, hence, enhancing economic performance [ 30 ]. Similarly, the sign of inflation is uncertain [ 21 , 23 25 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical appropriateness of the system GMM estimates is confirmed using the Hansen overidentification test (Hansen j ), the Arellano–Bond second-order serial correlation test (ARB) and avoiding the proliferation of instruments. The insignificance of the Hansen j and ARB indicates the absence of overidentification and second-order serial correlation respectively (Immurana et al , 2021e, 2021d; Roodman, 2009). Also, the number of instruments being less than the number of groups/countries confirms the absence of the proliferation of instruments (Roodman, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…We use life expectancy because it is a major indicator for measuring population health over the life cycle (Roser et al 2020). Also, death rate is employed because it encompasses all forms of mortalities (see Immurana 2020b; Immurana et al 2021a). The main independent variable used by the study is net FDI inflows (FDI), 2 while the growth rate of GDP (GDP), the number of physicians (Physicians), and gross secondary school enrolment (Education) are used as control variables.…”
Section: Methodsmentioning
confidence: 99%